(untitled) (Research, Society and Development, 2024)
The storage and loss modulus (G’; G"), cohesive energy, and viscosity of Hyaluronic Acids (HA) are key factors to be considered in aesthetic volumizing. Objective. This study aims to assess the properties of three HAs indicated for facial volumization: Gahya Volume, Gahya Light, and Gahya Classic. Methodology. Those rheological properties were performed in a rotational rheometer (TA-Instruments AR-1500ex). The sample volume for analysis was 1.0 mL. The frequency sweep was performed in the range of 10.0 to 0.01 Hz with 15 points. The following parameters were evaluated: viscoelasticity (G’ and G") considering the frequency variation, cohesive energy, and viscosity. The statistical method used to compare the results two by two was the unpaired t-test with significance level (p=0.05). Results. The results showed that G’ was statistically different when comparing Gahya Classic® and Gahya Light® samples and between Gahya Classic® and Gahya Volume® (p<0.05). Gahya Classic® and Gahya Volume® showed a significant difference from Gahya Volume® for G" (p<0.05). There was no significant difference between the samples for viscosity. Gahya Light® and Gahya Classic® have better elasticity and viscosity, and Gahya Light® and Gahya Volume® have better cohesive energy. Conclusion. Gahya Light® had the best behavior for the analyzed properties.